THE IMPACT OF GLOBALIZATION ON THE PENAL LEGISLATION OF UKRAINE - Lykhova, Sophia (Proceedings of National Aviation University (archive), 2016)
Purpose: The aim of this study is globalization, which affects all sectors of Ukrainian society, science, the development of science of criminal law, the legislative process and practice of regulatory policy. Globalization in criminal law in our opinion reveals in the process of harmonization of legislation, which is directed to the approaching and adjustment of normative legal precepts for the achievement of international, European and national legal standards. The harmonization helps in achieving of mutual consent for legal systems or for their structural parts within certain community. Methods: The main methods of unification in law are systematization of rules of national legislation, the implementation of legal propositions of international law into domestic legislation and its adaptation to international requirements. It should be highlighted such methodological reasons for harmonization as unity, integrity, proportionality, coherence and excellence. Results: It is shown that there are many problems of globalization in the criminal legislation area. Particular attention is paid to the problem of implementation of rules of criminal liability for legal persons for corruption offenses into domestic law. It is concluded that realization of this idea is impossible and inappropriate in present conditions because of the principle of individual and guilty liability, which should be considered as the important achievement of human civilization. Discussion: In our opinion we should investigate concrete legal systems of single countries instead of investigation of Anglo-Saxon legal system or Romano-Germanic system of law. Also the concept which used to understand as “family of law” should be scrutinized as some specifications of certain legal systems in different countries. Those specifications could be present or could be absent in certain legal system of each country. This issue is given much attention in the work of local scientists in the field of criminal law and comparative law Y. Baulin, V. Grischuk, V. Tihiy, V. Tuliacov, etc. But the unresolved problems related institute of criminal liability of legal persons, penalties, institute of measures of legal influence and others that have undergones significant changes under the influence of globalization.